THE EFFECT OF WHOLE BRAIN TEACHING STRATEGY ON THE STUDENTS’ SIMPLE PRESENT TENSE MASTERY AT THE EIGHTH GRADE OF SMP NEGERI 5 TAKENGON - Didik Arya Putra (Faculty of Tarbiyah nad Teacher Training, 2021)
This research aims to find out whether the whole brain teaching strategy has a significant difference in students' simple present tense mastery between students who taught by whole brain teaching strategy and those who taught by using the conventional strategy at eighth grade of SMP Negeri 5 Takengon. This research uses the quantitative research method (quasi-experimental research). The population of this research was the eighth grade of SMP Negeri 5 Takengon. There were four classes in the eighth grade and the researcher took two classes for the sample. There were 16 students for the experimental class and there were also 16 students for the control class. The instrument for collecting the data in this research was tested in the multiple-choice form. Before conducting the treatment, the researcher gave a pre-test and a post-test. In treatment, students in the experimental class were taught by using the whole brain teaching strategy and students in the control class were taught by lecture or conventional strategy. The result of this study shows that Ho is accepted and Ha is rejected. So, it can be concluded that there is no significant difference in students' simple present tense mastery between students who taught by the whole-brain teaching strategy and the conventional strategy at eighth grade of SMP Negeri 5 Takengon. Keywords: Whole Brain Teaching Strategy, Conventional Strategy, Simple Present Tense Master